Optimalisasi Pembelajaran Matematika DenganStrategi Scramble Untuk Peningkatan Keaktifan PadaSiswa Kelas VII Semester Genap MTs Negeri Surakarta IITahun 2014/2015 - Jati, Ayu Mustika; , Prof. Dr. Sutama, M.Pd (2016)
This study aims to describe the increase liveliness for the students classes VIIB MTs Country, Surakarta II with learning strategies scramble. This research uses research action class. Data source derived from the teachers and students. The implementation of the class action was carried out during two cycles consisting of 4 meetings. Method of data collection was done through tests, observation, field notes, interviews and documentation. Data analysis techniques used by qualitative descriptive through three stages, namely the reduction of data, exposure data, and a false assertion. The validity of the data with the triangulation of methods and sources. The first research results, the application of learning strategies can increase the liveliness of scramble intersection grade VIIB MTs Negeri Surakarta II. Both increase the liveliness of students namely 1) students dare to ask questions of the initial conditions (12.82%), on cycle I (38.46%), and in cycle II (76.92%), 2) students are able to work on the question of the exercise in front of a class of initial conditions (10.25%), on cycle I (41.02%), and in cycle II (71.79%), 3) students are able to answer questions from the initial conditions (12.82%), on cycle I (41.02%), and in cycle II (74.35%). Based on explanation above it was concluded that with the application of learning strategies can increase the liveliness of students scramble.